2012
DOI: 10.1371/journal.pone.0030249
|View full text |Cite
|
Sign up to set email alerts
|

IPET and FETR: Experimental Approach for Studying Molecular Structure Dynamics by Cryo-Electron Tomography of a Single-Molecule Structure

Abstract: The dynamic personalities and structural heterogeneity of proteins are essential for proper functioning. Structural determination of dynamic/heterogeneous proteins is limited by conventional approaches of X-ray and electron microscopy (EM) of single-particle reconstruction that require an average from thousands to millions different molecules. Cryo-electron tomography (cryoET) is an approach to determine three-dimensional (3D) reconstruction of a single and unique biological object such as bacteria and cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
221
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(228 citation statements)
references
References 78 publications
1
221
0
Order By: Relevance
“…Before studies employing contrast variation small-angle neutron scattering (SANS) (see below), the overall conformation of apoA1 within a lipid containing HDL particles was inferred from crystal structure data from lipid free apoA1 mutant forms ( 19,20 ), as well as measured distance constraints between inter-and intrachain amino acids in mutated or derivatized apoA1 using FRET or ESR ( 12 ), and in native apoA1 by cross-linking MS studies ( 11,15,21,22 ). Further structural information has been obtained from amide bond hydrogen/deuterium exchange mass spectrometry ( 14,23,24 )}, and cryo-electron tomography ( 25 ).…”
Section: Preparation Of Nhdl Dmpc With and Without Cholesterolmentioning
confidence: 99%
“…Before studies employing contrast variation small-angle neutron scattering (SANS) (see below), the overall conformation of apoA1 within a lipid containing HDL particles was inferred from crystal structure data from lipid free apoA1 mutant forms ( 19,20 ), as well as measured distance constraints between inter-and intrachain amino acids in mutated or derivatized apoA1 using FRET or ESR ( 12 ), and in native apoA1 by cross-linking MS studies ( 11,15,21,22 ). Further structural information has been obtained from amide bond hydrogen/deuterium exchange mass spectrometry ( 14,23,24 )}, and cryo-electron tomography ( 25 ).…”
Section: Preparation Of Nhdl Dmpc With and Without Cholesterolmentioning
confidence: 99%
“…Of note, it has been suggested that direct Fourier inversion can produce more accurate 3-D reconstructions (Heymann et al 2008) than the more traditional WBP and SIRT (Radermacher 2006) methods used in the field. Furthermore, since gold fiducials are absent from tilt series in cases where they might interact with the specimen and, when present, they undergo beam-induced motion resulting in unavoidable errors in whole-frame alignment (Comolli, & Downing 2005), subtiltseries can allow for more accurate individual per particle alignment, refinement and reconstruction, provided that the data have enough contrast, as demonstrated for negatively stained data (Iwasaki et al 2005) and cryoET data (Zhang, & Ren 2012).…”
Section: Introductionmentioning
confidence: 99%
“…FETR can tolerate certain levels of image distortion and measuring tilt-errors, and can also precisely determine the translational parameters via an iterative refinement process that contains a series of automatically generated dynamic filters and masks. Since this approach can obtain the structure of a single-instance macromolecule, we named it individual-particle electron tomography (IPET) as a new robust strategy/approach that does not require a pre-given initial model, class averaging of multiple molecules or an extended ordered lattice, but can tolerate small tilt-errors for high-resolution single ''snapshot'' of molecule structure determination (Zhang & Ren, 2012). FETR/IPET provides a completely new opportunity for a single-macromolecule structure determination, and could be used to study the dynamic character, equilibrium fluctuation, to reveal macromolecular mechanism, and even to track the intermediate state of the reaction of macromolecules Zhang & Ren, 2010).…”
mentioning
confidence: 99%